Penetrating dural venous sinus injury: a scoping review of clinical presentation, operative management, and prognosis - Yaxel Levin-Carrion; Jayant Bhasin; Taylor Campbell; Ebrahim Faizullabhoy; Kevin Titkov; Carlos Coronado-Guzman; Arman Sawnhey; Sraavya Anne; Daniela A. Perez-Chadid; Drew Thibault; Alejandro Pando; Nemanja Novakovic; et al. (Neurosurgical Review, 2026)
Abstract Penetrating injury to the dural venous sinuses (DVS) commonly occurs at the superior sagittal sinus (SSS), transverse sinus (TS), and torcular confluence. While rare, DVS penetrating injuries carry high risk of intracranial hemorrhage, air embolism, and venous infarction. The current literature pertaining to penetrating DVS injury consists primarily of isolated case reports and small series. This scoping review consolidates published cases to characterize mechanisms, management strategies, and clinical outcomes pertaining to penetrating DVS injury. A scoping literature search of PubMed, PubMed Central, Embase, and Scopus was performed through September 2025. English-language case reports, case series, and retrospective studies describing penetrating cranial trauma involving the SSS, TS, or torcula were included. Data were summarized descriptively. Twenty-five studies met inclusion criteria, encompassing low-velocity penetrating injuries, civilian firearm trauma, captive-bolt injuries, and wartime shrapnel. Low-velocity injuries were typically managed with wide exposure, circumferential sinus control, and either flow-preserving repair or selective SSS ligation, with favorable neurological outcomes. Firearm-related injuries demonstrated greater variability, ranging from excellent recovery after torcular reconstruction to delayed sinus thrombosis and fatal pulmonary air embolism following incomplete SSS sealing. Reconstruction was generally favored for posterior SSS, torcular, and dominant TS injuries, whereas ligation was better tolerated for anterior or mid-SSS lesions. Penetrating DVS injuries require early venous imaging, meticulous sinus control, and segment-specific decisions regarding repair versus ligation. Flow-preserving reconstruction is increasingly feasible and may optimize survival and neurological recovery.